Analisis Hubungan Antara Penilaian Kompetensi Profesional Dosen oleh Mahasiswa dan Kehadiran Mahasiswa terhadap Nilai Kelulusan Mahasiswa Menggunakan Fuzzy Quantification Theory I - Yuni Wiwiet Wiharti; Hindayati Mustafidah; Muhammad Hamka (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2012)
Competence of lecturer is one of the factors that influence the achievement of learning and education, but the competence of teachers or lecturers do not stand alone, but affected the educational background, teaching experience, and length of teaching. These competencies include pedagogic competence, professional, personal and social. To perform the analysis in this case using Fuzzy Quantification Theory I (FQT) is a qualitative assessment of the relationship between the factors of professional competence of students to faculty and student attendance for the graduation of students. The results of this study demonstrate that the professional competence of lecturer who most influence on the final value of students is the ability to give relevant examples of the concepts being taught, which has a value of 3.2717 weight category with a contribution of 1.1255